2023
DOI: 10.1136/jitc-2022-005518
|View full text |Cite|
|
Sign up to set email alerts
|

Intravesical BCG in patients with non-muscle invasive bladder cancer induces trained immunity and decreases respiratory infections

Abstract: BackgroundBCG is recommended as intravesical immunotherapy to reduce the risk of tumor recurrence in patients with non-muscle invasive bladder cancer (NMIBC). Currently, it is unknown whether intravesical BCG application induces trained immunity.MethodsThe aim of this research was to determine whether BCG immunotherapy induces trained immunity in NMIBC patients. We conducted a prospective observational cohort study in 17 NMIBC patients scheduled for BCG therapy and measured trained immunity parameters at 9 tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 107 publications
(103 reference statements)
3
12
0
Order By: Relevance
“…Patients with preexisting BCG-specific immunity, as measured by a positive purified protein derivative (PPD) skin test, or BCG-specific T cells, have longer RFS, suggesting that initially priming local immunity may improve BCG therapy response. A robust local and systemic immune response associated with long-term systemic trained immunity can be achieved with intravesical BCG instillation alone, and these studies suggest that first exposure to BCG primes the immune system to enhance the antitumor effect of a second exposure. The forthcoming SWOG S1602 results are anticipated to deepen our understanding of BCG priming.…”
Section: Discussionmentioning
confidence: 95%
“…Patients with preexisting BCG-specific immunity, as measured by a positive purified protein derivative (PPD) skin test, or BCG-specific T cells, have longer RFS, suggesting that initially priming local immunity may improve BCG therapy response. A robust local and systemic immune response associated with long-term systemic trained immunity can be achieved with intravesical BCG instillation alone, and these studies suggest that first exposure to BCG primes the immune system to enhance the antitumor effect of a second exposure. The forthcoming SWOG S1602 results are anticipated to deepen our understanding of BCG priming.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, these responses were maintained despite antimycobacterial drug treatment initiated by 4 weeks after administration of IV BCG. BCG has been shown to enhance innate immunity against TB through epigenetic modifications of hematopoietic stem cells, referred to as trained immunity [43][44][45][46] . Although this was not investigated in the current study, trained immunity in the context of pre-existing SIV and BCG vaccination will be a focus in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…52 The intra-bladder administration of BCG induces hyperactive monocytes, and patients who received intra-bladder BCG had a decreased rate of upper respiratory infections indicative of the induction of general trained immunity in these patients. 53 While BCG administered via other routes (intradermally for the TB vaccine and intravenously in animal models) can induced systemic reprogramming of hematopoiesis 24,54,55 it has been unclear if its use in the bladder and as a cancer microbial immunotherapy are via local bladder epithelial effects or systemic and hematopoietic reprogramming, and if the later, what the relevance of BCG immunotherapy might be of diverse other tumors. 50 We aimed to address the anti-tumor mechanisms induced by intra-bladder BCG and we have now demonstrated that bladder administration of BCG induces epigenetic and transcriptional changes in HSPC in mouse and human.…”
Section: Towards Mechanisms Linking Trained Immunity To Adaptive Immu...mentioning
confidence: 99%